The Role of Ecopreneurship in Bali’s Sustainable Tourism Development: Insights into Government Policy, Tourist Awareness and Preferences - MANANDA, I G.P.B Sasrawan; SUDIARTA, I Nyoman (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).10, 2024)
There are numerous environmental issues in Bali, a popular tourist destination in Indonesia, including the problems of waste, critical land, beach abrasion, coral reef destruction and water contamination, all attributed to the rapid expansion of the tourism industry. Ecotourism is one of the solutions to address these concerns, and the initiatives taken involve ecopreneurship, the process of starting and running green firms that support sustainable tourism growth in Bali. The goal of ecopreneurship in the tourism industry is to create and run enterprises that have as minimum negative environmental impacts as possible, while maximising positive social and economic consequences. This is done through improvements on both public policies and tourist preferences, to promote a sustainable tourism development. A mixed method was used, combining SEM PLS, Path Methods, and qualitative research, with comprehensive interviews conducted among ecopreneurs, government agencies, tourists, and academics in Bali. Ecopreneurship variables, comprising environmentally friendly products and services, green technology innovation, environmental and natural resource management, local community involvement, environmental education and awareness, waste and emission management, collaboration and partnerships, measurement of environmental performance and sustainability, moderated by the government policy and tourist awareness and preference, were found to have a  significant influence on sustainable tourism variables, namely, natural environment preservation, social welfare and culture, local economic empowerment, resource management and environmental impact reduction, local community participation and public consultation .